University social responsibilities for English Language education in Malaysian Higher Education: community-based service learning - Abdullah, Nur Nabilah; Sahar, Rafidah; Ramdzan Ali, Al Amirul Eimer (Raffles University Iskandar, 2023)
Malaysian higher institutions play an important role in producing quality employable graduates with a good command of English. A study administered by the Ministry of Higher Education, the National Blueprint of Graduate Employability 2012-2017, found that graduates’ poor command of English is the highest identified by employers. The concept of 'Sustainability Education' at the tertiary level can be viewed as an important element that promotes experiential learning with community partners to improve students' communication skills and graduate employability. Service learning is the most effective method for addressing the issue of Sustainability Education, and it may be considered as lending credence to the emerging idea of University Social Responsibilities (USR) in Malaysian higher education. The purpose of this study is to explore the potential of a service learning approach as a concept of University Social Responsibility for fostering sustainable English language education at Malaysian higher education institutions